Oxygen profiles of surface sediments retrieved from the southern Weddell Sea shelf during RV POLARSTERN cruise PS111 - Baloza, Marwa; Maier, Sandra; Hanfland, Claudia; Henkel, Susann; Kasten, Sabine; Richter, Claudio; Holtappels, Moritz (In: Baloza, M et al. (2025): Oxygen profiles and pore-water geochemistry of surface sediments collected from the southern Weddell Sea shelf [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.987276, 2025)
During the PS111 research cruise with the German research vessel RV POLARSTERN (January 2018- March 2018), sediments were collected with a multicorer from 15 stations, i.e., four on the eastern Weddell Sea shelf at 387 to 663 m water depth, five in the Filchner Trough at 794 to 932 m water depth, and four along the western Weddell Sea shelf at 332 to 660 m water depth. Two deeper stations were located on the eastern Weddell Sea slope at 1405 and 1775 m water depth. A total of 28 high-resolution O2 profiles were measured in the upper sediment layer using optical microsensors (Optodes, Pyroscience) in order to determine diffusive oxygen uptake (DOU).
Keywords: Antarctic; oxygen uptake; shelf sediments